Practical Trial for Low-Energy Effective Jamming on Private Networks With 5G-NR and NB-IoT Radio Interfaces - Pawel Skokowski; Krzysztof Malon; Michal Kryk; Krzysztof Maslanka; Jan M. Kelner; Piotr Rajchowski; Jaroslaw Magiera (IEEE Access, 2024)
Fourth-generation (4G) mobile networks are successively replaced by fifth-generation (5G) ones, based on the new releases of the 3rd Generation Partnership Project (3GPP) standard. 5G generation is dedicated to civilian users and the conducted analytical work shows that it has numerous technological gaps that prevent its direct implementation in military communications systems. However, the recent armed world conflicts showed that closed or public mobile networks are willingly used by soldiers for both private and business communications, and to conduct defensive and offensive operations as well. From the military operation viewpoint, jamming both civil and military systems is one of the essential elements of electronic warfare. This paper focuses on the practical trial of low-energy and smart jamming on a 5G private network using narrowband signals, which facilitates the reduction of the available throughput, e.g. in the time division duplex - uplink (TDD-UL) by 99%, or by 82% in the frequency division duplex - downlink (FDD-DL). This type of jamming also allows for reaching up to 25 dB of energy gain comparing to barrage jamming. The authors moreover investigated jamming the Narrowband IoT radio interface using synchronized, selective jamming. The goal was to propose energy efficient methods that will allow the jammers to work longer and be mounted on a small unmanned aerial vehicle (UAV) that can operate near the gNB. The generation of low-power jamming signals in the gNB vicinity successfully hinders detecting the jammer by the enemy’s electronic reconnaissance systems. The proposed solutions are compared with the test results for other types of jamming methods.